African-American and white living standards in the 19th century American South : a biological comparison - Scott Alan Carson (Center for Economic Studies and ifo Institute (CESifo), 2006)
By using a new source of 19th century Texas state prison records, the present study contrasts the biological living conditions of comparable blacks and whites in the American South between the Civil War and Reconstruction. White stature exceeded black stature. Between 1850 and 1870, black sub-adult stature declined by over one centimeter. Postbellum sub-adult white stature declined by over one and a half centimeters and never recovered over the same period. The secular trend for adult blacks improved by two and one half centimeters between the 1850s but declined after the Civil War.
Keywords: N31; I12; J70; J15; I31; 330; Lebensstandard; Gesundheit; Schätzung; USA <Südstaaten>; Körpergröße